Invariant analysis and explicit solutions of the time fractional nonlinear perturbed Burgers equation - Wang, Gangwei; Xu, Tianzhou (Nonlinear Analysis: Modelling and Control, 2015)
The Lie group analysis method is performed for the nonlinear perturbed Burgers equation and the time fractional nonlinear perturbed Burgers equation. All of the point symmetries of the equations are constructed. In view of the point symmetries, the vector fields of the equations are constructed. Subsequently, the symmetry reductions are investigated. In particular, some novel exact and explicit solutions are obtained.
Keywords: perturbed Burgers equation; Lie group analysis; symmetry reductions; power series method; explicit solutions